A sample integrity analysis of faunal remains from the RSp layer at Sibudu Cave - Wells, C. R. (Southern African Humanities, 2021)
I examine Middle Stone Age faunal remains from Sibudu Cave's RSp layer, which has an age of ~50 ka. The study focuses on taphonomy, taxonomic composition, skeletal part representation and bone modification. The assemblage was found to have suffered from severe fragmentation and minimal density-mediated attrition, but it is argued that it contains valuable information about human behaviour during the MSA in southern Africa. The site inhabitants appear to have been the principal accumulating agents at the site because there are high frequencies of humanly-induced bone modifications and very little evidence of non-human carnivore involvement. The focus was on medium-to-large ungulates, and dangerous as well as docile animals were hunted. The wide array of species present indicates that there was a dry, yet diverse, environment, which included grassland and woodland. To cite this article: Wells, C. R. 2006. A sample integrity analysis of faunal remains from the RSp layer at Sibudu Cave. Southern African Humanities 18 (1): 261-77.